Including stakeholder perspectives in digital forensic programs - Armstrong, Colin (The Institute of Electrial and Electronics Engineers, Inc, 2012)
An investigation due to adverse outcomes in a computer incident encapsulates stakeholders acting in specific roles. These stakeholders will have a unique worldview, based upon their association with other actors or the items of evidence. The worldviews of each actor will lean either side of neutrality towards either the prosecution or defense perspective. This paper discusses the inclusion of stakeholder perspectives into a traditional university program for a digital forensic curriculum.